Augustine on Sacrifice: A Synthesis - Janeczko, OFM Cap., Fr. Matthew (Lumen et Vita, 2014)
This essay investigates the manner in which Augustine writes about the related topics of sacrifice, priesthood, and mediation. Drawing upon the Confessions, The Trinity, and the City of God, as well as relevant secondary literature, it concludes that an understanding of Augustine's views regarding these topics allows for a broader comprehension of the proper ends of Christian life: true acts of charity and worship.